436 A peri-myocarditis unmasks an underlying hypertrophic cardiomyopathy. (8th December 2021) - Rubino, Francesca; Capocci, Sofia; Portolan, Leonardo; Gambaro, Alessia; Pighi, Michele; Ribichini, Flavio Luciano
Abstract: Methods and results: A 41-year-old black man complaining of severe oppressive chest pain radiated to the back presented to our accident & emergency department (A&E). His symptoms started few days before his hospital admission. Past medical history was remarkable for arterial hypertension in medical therapy and microdrepanocytosis. In A&E, the patient's physical examination and vital signs were normal, he was normotensive, apyretic with normal oxygen saturation. The ECG showed ST elevation in anterior and lateral leads. Because of his history of arterial hypertension, and the severe chest pain irradiated to the back, an angio-CT was indicated at first. The CT ruled out acute aortic disease. Excluded the acute aortic disease, the patient underwent an urgent coronary angiography. No coronary stenosis was found. Therefore, the patient was admitted in cardiac intensive care unit. The blood test showed an elevation of high sensitive cardiac troponin T (cTnT peak 3093 ng/L) and inflammatory index (leukocytosis 13.65 10 9 /l and protein C reactive peak 347 mg/L). An in-depth anamnestic collection revealed fever with respiratory symptoms about 2 weeks before. The echocardiography demonstrated left ventricular (LV) dysfunction with increased ventricular wall thickness and mild pericardial effusion. No LV outflow tract obstruction was found. A provisional diagnosis of peri-myocarditis was made. During hospitalization, anti-remodelling cardiac therapy was introduced and up titrated. To confirm the provisional diagnosis, a Gadolinium cardiac Magnetic Resonance (CMR) was performed, and it revealed myocardial oedema on basal anterior interventricular septum and multiple areas of late gadolinium enhancement with subepicardial pattern. Moreover, severe LV hypertrophy was confirmed (interventricular septum 19 mm, inferior wall 17 mm). This pattern was consistent to the diagnosis of peri-myocarditis on a hypertrophic cardiomyopathy (HCM). Main infectious causes of peri-myocarditis were investigated, but the results were inconclusive. Unfortunately, genetic test results are still not available. Patient was discharged with recovered LV systolic function and free of symptoms on optimal medical therapy; no ventricular arrhythmias was detected during hospitalization. HCM risk sudden cardiac death (SCD) was lower than 4%. Conclusions: Peri-myocarditis can mimic symptoms of an acute coronary syndrome. Furthermore, the inflammation of cardiac muscle and the subsequent interstitial oedema may cause an increase in LV wall thickness. In this setting, the diagnosis of an underlying cardiomyopathy is challenging. This interesting and unusual case highlights the relevance of an accurate diagnostic work up to deliver good clinical practice. In particular, Gadolinium CMR is of paramount importance in this setting.